2014
DOI: 10.1364/ol.39.003970
|View full text |Cite
|
Sign up to set email alerts
|

Elastic property attributes to photoacoustic signals: an experimental phantom study

Abstract: We report an experimental study that shows the attribution of the elastic property of light absorbing targets to the generation of ultrasound signals induced due to the photoacoustic effect. We investigated the variation in strength of the detected photoacoustic signals for various targets embedded in a background phantom with: (1) different elastic coefficients (94-346 kPa) and (2) various sizes (0.25-1.5  mm²). The results show that photoacoustic signals increase with an increase in elastic coefficient (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…[76][77][78][79][80][81][82][83] Recently, research studies were reported for possible recovery of the elastic property of soft biological tissue with PA imaging technology. [84][85][86][87][88][89][90][91][92] This innovative study enhances the horizon of potential applications of PA imaging extending to diagnosis and therapeutic treatment of life-threatening diseases (such as breast and prostate cancer, 4 brain tumor, 93 and Alzheimer's diseases 94 ) that induce contrast in elasticity relative to normal tissues. Currently, PA elastography (PAE) imaging is limited only to qualitative study, and it is in the nurture stage of development.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…[76][77][78][79][80][81][82][83] Recently, research studies were reported for possible recovery of the elastic property of soft biological tissue with PA imaging technology. [84][85][86][87][88][89][90][91][92] This innovative study enhances the horizon of potential applications of PA imaging extending to diagnosis and therapeutic treatment of life-threatening diseases (such as breast and prostate cancer, 4 brain tumor, 93 and Alzheimer's diseases 94 ) that induce contrast in elasticity relative to normal tissues. Currently, PA elastography (PAE) imaging is limited only to qualitative study, and it is in the nurture stage of development.…”
Section: Introductionmentioning
confidence: 88%
“…84 In this study, a phase-resolved technique was employed. Singh and Jiang 85 reported an experimental study that demonstrates attribution of elastic properties of light absorbing targets to the generation of ultrasound signals induced due to PA effect, i.e., generation of acoustic waves upon illumination of a sample material by a short duration (ns) pulse optical beam. The study investigated variation in the strength of PA signals for various targets, with different elastic coefficients and various sizes, embedded in a background phantom.…”
Section: Photoacoustic Elastography Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 PA tomography has been applied for noninvasive temperature measurement, since the PA signal amplitude is linearly dependent on temperature in the range from 10 C-55 C. 18,20,21 In addition, a dual-wavelength PA technique has been developed to monitor tissue optical properties during thermal treatment, based on the observation that the ratio of PA signals generated by the two wavelengths is independent of temperature. 23 However, most studies focus only on measured PA signals in the sample boundary 24 with enhanced light absorption in target tissue. 18 The PA response from tissues far from the boundary or without photoabsorbers often has low signal intensity.…”
Section: Introductionmentioning
confidence: 99%